PENGARUH STRES KERJA TERHADAP KINERJA KARYAWAN PT BUANA TRANSPERINDO WAHANA INTERNASIONAL MELALUI GENDER SEBAGAI VARIABEL KONTROL - Suali; Heryenzus (ADAI Kepri, 2022)
One of the factors that influence the success rate of a company is the employee’s performance. High employee performance contributes optimally to the company. To improve employee performance, a company must pay attention to job stress. Job stress can affect performance both positively and negatively. Gender equality in employee position placement also contributes to the performance performance itself. Socio-cultural constructions of the community have included a common view for each gender that assesses women's performances are not as good as performance of men in the world of work. This research intended to analysis the influence of work stress and gender on employee performance of PT. Buana Transperindo Wahana International. The method used in this study is the census method, with a sample of 94 men and 15 female samples. Primary data collection was done by questionnaire method. Result data of filling questionnaire processed by using Program SPSS 21. Analysis technique in this research use multiple linear regression analysis, F test and t test. The results showed that job stress partially significant effect on employee performance. Gender partially significant effect on employee performance. Work and gender stress simultaneously have a significant and positive effect on employee performance.